Pemeriksaan Tekanan Darah sebagai Upaya Preventif Kesehatan Masyarakat untuk Meningkatkan Kesadaran Pola Hidup Sehat - Jimat, Resi Tondho; Emma Ismawatie; Yulita Maulani; Arum Kusuma Putri; Rahmayani Agustin Nanda Kusuma; Rudiharto (Gayaku Publisher, 2025)
Hypertension is one of the most common non-communicable diseases that often presents without symptoms but carries a high risk of severe complications such as heart disease and stroke. Preventive and promotive efforts, such as health education and regular blood pressure screening, play a crucial role in increasing public awareness of healthy lifestyles. This community service activity was conducted in Jayan Village, Boyolali, through educational sessions and health screenings involving local residents as participants. The results showed that 81% of participants were identified as having hypertension at various levels. This program successfully improved community understanding of early detection of high blood pressure and encouraged lifestyle modifications. Routine blood pressure checks proved to be an effective preventive strategy for controlling hypertension at the community level.